The Role of Responsibility Feeling in Mediating the Effects of the Environmental Education Course, Socio-Economic Conditions, and Awareness as the Caliph on Environmental Behavior - WIDHIASTUT, Ratieh; SETIYANI, Rediana; KARDIYEM, KARDIYEM; RAHMANINGTYAS, Wisudani (Journal of Environmental Management and Tourism, 2019)
This study aims to determine the direct and indirect effects of the role of enviromental education course, socio-economic conditions, and the awareness of the caliph on the environmental behavior through responsibility feeling. The research sample was all students of accounting education in 2016. The research data were primary data obtained by using a questionnaire. Data analysis used Structural Equation Modeling (SEM). The results showed that the variables of environmental education course, socio-economic conditions, and awareness as caliphs had no direct efect on the environmental behavior, only responsibility feeling variable that could affect the environmental behavior. The variables of environmental education course, and awareness as caliphs had no direct effect on the responsibility feeling while the variable of socio-economic conditions had direct effect on the responsibility feeling. Responsibility feeling was able to mediate the effect of the variables of socio-economic conditions and awareness as a caliph on the environmental behavior, but was not able to mediate the relationship of the effect of the variable of environmental education course on the environmental behavior.